An Investigation of People's Attitudes about Bicycling in Urban Areas in the US: An Exploratory Case Study in Washington DC - SHEN, YAQI. (2017)
Abstract: Biking as the travel mode has become more and more common and popular recently. However, some problems occurred in development of cycling. This thesis explores the use of mico-blog data in the form of sentiment analysis and statistical analysis to determine if there are relationships existed between people's attitude, bicycling index, and locations where people talking about bicycling. Furthermore, this thesis lays the groundwork for a deeper understanding of bikeability by making quantitative analysis. My results demonstrate that there is relationship existed between peoples' attitude and few bicycling facilities and physical environment factors. Furthermore, some correlation results between each independent variables and sentiment scores indicated. I also provide suggestions about some good strategies of developing cycling for bicycling planners and policy makers by using the results indicated in this study; Thesis (M.A.)--Tufts University, 2016.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Justin Hollander.; Committee: Sumeeta Srinivasan.; Keyword: Regional studies.